Autonomía del paciente oncológico en la toma de decisiones previas a procedimientos quirúrgicos, revisión sistemática - Mendoza Zambrano, Gabriel Agustín (2026)
Introduction: Cancer is a complex disease that affects millions of people worldwide, and its treatment requires a comprehensive approach that addresses the physical, emotional, and social needs of patients. In this context, the autonomy of oncology patients in decision-making prior to surgical procedures is essential to ensure patient-centered care and improve their quality of life. Objective: To describe the autonomy of oncology patients in decision-making prior to surgical procedures through a systematic review. Methods: A systematic review was conducted following the PRISMA methodology. The literature search was carried out in scientific databases, resulting in 42 selected documents. The review included original articles, systematic reviews, books, and doctoral theses published between 2021 and 2025 in Spanish, English, and Portuguese. A critical evaluation of the selected literature and a comparative analysis of the evidence were performed. Results and Discussion: The findings indicate that oncology care should prioritize patient autonomy in decision-making before surgical procedures, ensuring comprehensive and humanized care. This requires fostering effective communication and encouraging patient participation, which are essential for delivering high-quality care. Advanced nursing plays a crucial role in this process, as it can address the individual needs of patients and enhance the quality of pre-surgical care. Additionally, humanization in oncology treatment is vital to promote the physical, psychological, and emotional well-being of patients.